Socio-Economic Determinants of Urbanization in the Perspective of Pakistan - Arif, Muhammad; Gill, Abid Rashid (Pakistan Journal of Humanities and Social Sciences, 2023)
This analysis examines the socioeconomic determinants of urbanization in Pakistan by using data from 1970 to 2020. For data estimation, an ARDL technique and error correction model is used. The main outcomes show that the variables gross domestic savings, inflation rate, industrialization, education, population growth rate, and GDP per capita are positively associated with urbanization, while the variables financial development and exports are negatively associated with urbanization in Pakistan. However, the impact of inflation rate, remittances, exports of goods and services and GDP per capita on urbanization is statistically insignificant. Considering the study outcomes, it is suggested that to control the increasing growth of urbanization in Pakistan, it is important to design policies to improve the basic necessities in rural areas and strengthen the agriculture sector to discourage rural-to-urban migration.